2022
DOI: 10.35971/jjhsr.v4i3.12488
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Risk Factors in Elderly Patients at Royal Prima Medan General Hospital

Abstract: Sepsis is a severe infectious disease accompanied by the discovery of a systemic response that can include hypothermia, hyperthermia, tachycardia, hyperventilation, and fatigue. Some studies suggest age is the most common risk factor for sepsis. The goal of the study was to determine the risk factors for sepsis in elderly patients associated based on age, gender, diagnosis, location of the infection, and length of treatment. The study used 100 samples of elderly patients aged 60 years diagnosed with sepsis. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The initial diagnosis of patients arriving at the inpatient facility was with an endocrinology diagnosis for 13 (15.38%) patients, followed by neurology 10 (15.38%), gastroenterology 9 (13.85%) and respiration 6 (9.63%). The research results are in line with Djuang, et al (2022) the largest percentage is endocrine (23.5%) According to theory based on endocrinology diagnosis, the comorbid disease most frequently affected by sepsis is diabetes mellitus [5] . According to research by D'Almeida, et al, (2021), sepsis in adults with type 2 diabetes mellitus treated at Tupua Tamasese Meaole Hospital has a higher prevalence rate in women, 55% and 62.5%, respectively [9] .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The initial diagnosis of patients arriving at the inpatient facility was with an endocrinology diagnosis for 13 (15.38%) patients, followed by neurology 10 (15.38%), gastroenterology 9 (13.85%) and respiration 6 (9.63%). The research results are in line with Djuang, et al (2022) the largest percentage is endocrine (23.5%) According to theory based on endocrinology diagnosis, the comorbid disease most frequently affected by sepsis is diabetes mellitus [5] . According to research by D'Almeida, et al, (2021), sepsis in adults with type 2 diabetes mellitus treated at Tupua Tamasese Meaole Hospital has a higher prevalence rate in women, 55% and 62.5%, respectively [9] .…”
Section: Discussionsupporting
confidence: 88%
“…Based on the research results, the gender of critical sepsis patients in Inpatient Installation Dr. Soetomo 1 February -31 March 2023 was obtained the majority were women with 34 patients (52.31%) followed by men with 31 patients (47.69%). The results of this research are in line with research conducted by Hatman et al (2021) at Dr. Soetomo, Surabaya, where the majority of sepsis patients were women (57.14%) compared to men (42.86%) [4] .Another research study Djuang, et al (2022) at the Royal Prima General Hospital, Medan, the results of the gender category research were that women were the most numerous (55.7%) compared to men (44.7%) [5] . This research shows the age of critical sepsis patients, namely there are several categories in late adolescence (1.54%) aged 17 to 25, followed by early adulthood (4.62%) aged 26 to 35, then late adulthood (12.31%) %) around the age of 36 to 45, early elderly (18.46%) aged 46 to 55, late elderly (26.15%) aged 56 to 65, seniors (36.92%) over 65 years of age.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Another study revealed that sepsis patients were mostly suffered by the age group more than 65 years compared to other age groups. 5 In older age, there is a decrease in immune system function known as immunosenescence. Immunosenescence affects the capacity of both the innate and adaptive immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…This can occur as the body's immune system decreases with age. 5 Male gender has also been reported to be more likely to suffer from sepsis rather than female. This may be due to the influence of female sex hormones that are reported to affect the immune system, which may cause a protective effect in females.…”
Section: Introductionmentioning
confidence: 99%